2002
DOI: 10.1093/intimm/14.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Gene conversion–like sequence transfers in a mouse antibody transgene: antigen selection allows sensitive detection of V region interactions based on homology

Abstract: Gene conversion is important for antibody diversification in chickens, rabbits and cows. In mice, however, conversion events appear to be infrequent among endogenous antibody genes. DNA sequence transfer events that resemble gene conversions have been reported for a mouse H chain transgene (VVC(mu)) that contains two closely spaced homologous VDJ segments. Surprisingly, these reported VVC(mu) sequence transfers were found frequently among mouse B cells responding to immunization. Transgene sequence transfers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 47 publications
5
16
0
Order By: Relevance
“…Fourteen of these clones contained inserts derived from the transgene VDJ segments and five of the fourteen clones displayed sequence transfers (Fig. 5) like those that have been previously reported for other immunized VVC mice (12,13). All five of the RT-PCR products that had transgene conversion also had somatic mutations.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…Fourteen of these clones contained inserts derived from the transgene VDJ segments and five of the fourteen clones displayed sequence transfers (Fig. 5) like those that have been previously reported for other immunized VVC mice (12,13). All five of the RT-PCR products that had transgene conversion also had somatic mutations.…”
Section: Resultssupporting
confidence: 63%
“…Studies have also indicated that homology-based sequence transfers might play a significant role in Ig gene somatic hypermutation. Transgene V gene sequence transfers have been found to be frequently associated with high levels of somatic hypermutation (12,13), suggesting that homology-based recombination and somatic hypermutation might share some mechanistic steps (13,14). Furthermore, DNA cleavages associated with somatic hypermutation of endogenous Ig genes are predominantly found at the G 2 cell cycle stage; this observation is consistent with the hypothesis that homologybased repair might play a role in the hypermutational mechanism (15).…”
supporting
confidence: 80%
See 3 more Smart Citations